PENGARUH HARGA,KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RESTORAN O-MAMAMIA STEAK AND ICE CREAM CABANG JATI SEMARANG - Nadia Rizqiyatul Faizah; Sri Suryoko; Saryadi Saryadi (Universitas Diponegoro, 2013)
O-Mamamia restaurant Steak n Ice Cream Semarang is a steak restaurant providing ice cream at the same time, which has ten branches one branch is O-Mamamia Restaurant Steak n Ice Cream Jati Semarang. In an effort to maintain relationships with customers, service quality is the key to retaining customers and providing high value through customer value. Customers will compare the quality of services provided at a price that is charged for the steak provided. Currently there is a restaurant that provides a lot of steak menu, causing intense competition. Intense competition will directly affect the number of customers coming as it did on the O-Mamamia Restaurant Steak n Ice Cream Jati Semarang which decreased the number of customers each year. This study aimed to determine the effect of pricing, product quality and service quality on customer satisfaction O-Mamamia Steak n Ice Cream Teak Semarang. The population in this study is the customer O-Mamamia Restaurant Steak n Ice Cream Teak Semarang. The research sample of 100 respondents was taken and the sampling technique used is purposive sampling. Measurement scales using Likert scale. In the analysis of the data using simple linear regression and multiple regression test with the help of the program SPSS 18.00. Based on the survey results revealed the price variable has an influence on the customer satisfaction variables, where the t value (3.456)> t table (1.29025). That is, for a positive and significant impact on customer satisfaction. Value of the coefficient of determination of 0.109 or 10.9%. This means that 10.9% customer satisfaction variables can be explained by the variable price. Variable product quality has an influence on the customer satisfaction variables, where the t value (4.905)> t table (1.29025). That is, the product quality has positive and significant impact on customer satisfaction. Value of the coefficient of determination of 0.197 or 19.7%. Variable Quality of Service has a variable effect on customer satisfaction, which amounted to 8.451 t count> t table of 1.29025 means that service quality has positive and significant impact on customer satisfaction. Value of the coefficient of determination of 0.422 or 42.2% Suggestions put forward for O-Mamamia Restaurant Steak n Ice Cream Teak Semarang is need for adjustment between the tariff charged to consumers with the quality of services provided, maintaining the delicious taste, customer service should be further enhanced.